Teacher's Strategy to Support Student's Creativity in Cultural Arts and Craft Learning - Linda Sari Siregar (LANGGAM: International Journal of Social Science Education, Art and Culture, 2024)
This qualitative research study investigates mural decorations and student creativity within a school context. Specifically, the study examines the shape, pigment, and composition of mural art as essential elements. The research was conducted in 15 classrooms, with a sample of three classes selected for in-depth analysis. Data collection methods included observational techniques, detailed interviews, and visual records. Qualitative and descriptive analysis methods were applied to analyze the gathered data. The findings reveal that students’ appreciation of murals is influenced by the innovative use of figure, color, pattern, form, and design by the artists. The central concept revolves around portraying students’ character through murals, representing the principles of natural harmony in a simplified form. Notably, one recurring theme emphasizes the perception of freshness and the connection to the local environment, underscoring the importance of preserving ordinary surroundings.